2018
DOI: 10.1002/jbm.a.36557
|View full text |Cite
|
Sign up to set email alerts
|

Improved ex vivo expansion of mesenchymal stem cells on solubilized acellular fetal membranes

Abstract: Coatings produced from extracellular matrixes (ECMs) have emerged as promising surfaces for the improved ex vivo expansion of mesenchymal stem cells (MSCs). However, identifying a readily available source of ECM to generate these coatings is currently the bottleneck of this technology. In this study, we assessed if ECM coatings derived from decellularized fetal membranes were a suitable substrate for MSC expansion. We separated and decellularized the two main components of the fetal membranes, the amnion and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…We proposed that the ECM at each stage of development provides biological cues to promote regeneration or fibrosis and hypothesized that ECM derived from neonatal mice can prevent widespread ventricular remodeling following injury in an adult model of MI. Previous studies, particularly those investigating mesenchymal stem cells, have consistently shown that young ECM is able stimulate expansion of adult cells and contribute to osteogenesis more effectively than adult ECM [48][49][50]. Placental ECM has also been proposed to assist in a number of medical applications [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that the ECM at each stage of development provides biological cues to promote regeneration or fibrosis and hypothesized that ECM derived from neonatal mice can prevent widespread ventricular remodeling following injury in an adult model of MI. Previous studies, particularly those investigating mesenchymal stem cells, have consistently shown that young ECM is able stimulate expansion of adult cells and contribute to osteogenesis more effectively than adult ECM [48][49][50]. Placental ECM has also been proposed to assist in a number of medical applications [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Human term placentae from uncomplicated pregnancies were used to isolate primary MSCs from the decidua basalis according to our previously published protocol ( 1 , 30 32 ). Written and informed patient consent and ethics approval from the Royal Women's Hospital Human Research and Ethics Committee was obtained (HREC #14/35).…”
Section: Methodsmentioning
confidence: 99%
“…This is because only 0.001-0.01% of cells in the bone marrow are mononuclear cells [134]. After the expansion process, hBM-MSCs are detached from the culture dish and subjected to a serum-starved condition, which is largely different than their original environment, such as the MSC niche, and cells lose their useful properties [135][136][137][138]. Previous reports evaluated the freshness of hBM-MSCs kept in phosphate-buffered saline (PBS) over time after trypsinization, which can mimic ex vivo storage conditions [9,23].…”
Section: Improvements In the Quality And Freshness Of Bm-mscsmentioning
confidence: 99%